UNITED STATES DURING THE COLD WAR 1945-1990 - Novita Mujiyati; Kuswono Kuswono; Sunarjo Sunarjo (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2016)
United States and the Soviet Union is a country on the part of allies who emerged as the winner during World War II. However, after reaching the Allied victory in the situation soon changed, man has become an opponent. United States and the Soviet Union are competing to expand the influence and power. To compete the United States strive continuously strengthen itself both in the economic and military by establishing a defense pact and aid agencies in the field of economy. During the Cold War the two are not fighting directly in one of the countries of the former Soviet Union and the United States. However, if understood, teradinya the Korean War and the Vietnam War is a result of tensions between the two countries and is a direct warfare conducted by the United States and the Soviet Union. Cold War ended in conflict with the collapse of the Soviet Union and the United States emerged as the winner of the country.